Exploring the Role of IoT in Transforming Agriculture: Current Applications and Future Prospects - Maddali Anusha; Amitabh Soni; Rashmi Mohapatra; Vimal Kumar; M. R. Bhanusree; Damayanti Giri; Shubham Gupta (Archives of Current Research International, 2025)
The Internet of Things (IoT) has revolutionized modern agriculture by integrating smart technologies that enhance efficiency, sustainability, and productivity across various farming sectors. IoT applications in precision agriculture, livestock management, water resource optimization, post-harvest logistics, and supply chain management enable real-time monitoring, automated decision-making, and predictive analytics. Research indicates that IoT-based agricultural systems can increase crop yields by 25%, reduce irrigation water consumption by 50%, and lower post-harvest losses by 30%. IoT-driven precision farming utilizes smart sensors, AI-driven analytics, and automated systems to optimize soil moisture management, pest control, and nutrient application, ensuring resource-efficient production. In livestock management, IoT-enabled wearables and automated feeding systems improve animal health monitoring, enhance milk yield, and reduce disease-related losses. Water conservation through IoT-based smart irrigation and hydroponic systems has shown a 40% improvement in water-use efficiency, mitigating the impact of climate change. Post-harvest management and supply chain integration with IoT technologies have reduced food spoilage through real-time temperature monitoring, smart packaging, and blockchain-enabled traceability. Despite these advancements, challenges such as high implementation costs, cybersecurity risks, infrastructure limitations, and the need for skilled labour hinder widespread adoption. Studies indicate that nearly 45% of rural farms lack access to stable internet connectivity, restricting the deployment of IoT-based agricultural solutions. Overcoming these barriers through policy reforms, financial incentives, and digital literacy programs will accelerate IoT adoption and drive agricultural transformation. The future of IoT in agriculture lies in further integration with artificial intelligence, robotics, and blockchain for enhanced automation, food security, and climate resilience. As technology advances, IoT-driven smart farming will play a pivotal role in achieving global agricultural sustainability, ensuring higher productivity with reduced environmental impact.